Elastic interaction energy of point defects with a basal dislocation loop in zirconium - Trotsenko, O.G.; Babich, A.V. (Вопросы атомной науки и техники, 2020)
Based on the tensor Green's function for hexagonal crystals obtained by the Lifshitz-Rosenzweig method, the analytical expression of the elastic interaction energy of radiation point defects is calculated in the model of force dipoles with a dislocation vacancy loop (basal plane of occurrence {0001}, Burgers vector bᴰˢ = 1/6⟨2023⟩), in zirconium.